Production of medical isotopes at electron accelerators - Dikiy, N.P.; Dovbnya, A.N.; Lyashko, Yu.V.; Medvedeva, E.P.; Tur, Yu.D.; Uvarov, V.L.; Fedorets, I.D.; Pashchuk, S.A.; Evseev, I.G. (Вопросы атомной науки и техники, 2000)
A brief summary of the production medical isotopes by powerful linac electron accelerator is presented.